2010
DOI: 10.1021/jz900380a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Spectroscopy of the S2 State of CHF and CDF: Dynamically Weighted Multireference Configuration Interaction Calculations for High-Lying Electronic States

Abstract: Dynamically adjusting the weights in state-averaged multiconfigurational self-consistent field (SA-MCSCF) calculations using an energy-dependent functional allows the electronic wave function to smoothly evolve across the potential energy surface (PES) and correctly preserves differing asymptotic electronic-state degeneracy patterns. We have developed a generalized dynamic weighting (GDW) method to treat high-lying electronic states. To test the method, a global PES was constructed for the S 2 ( B) state of CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…It has recently been shown by Dawes et al 21,22 that the "reef"-like saddle point present in many previous ozone PESs is an artifact of the electronic structure model used to generate the PESs. The new Dawes-LolurLi-Jiang-Guo (DLLJG) PES, obtained with a dynamically weighted 23,24 explicitly-correlated multi-reference configuration interaction [25][26][27] approach with the Davidson correction 28 and spin-orbit correction (DW-MRCI-F12+Q), is "reef"-free, thus qualitatively different from all previous ozone PESs. 16,20,29 The disappearance of the "reef" structure essentially results from the employment of a large basis set, larger active configuration spaces, and dynamical weighting of excited states.…”
mentioning
confidence: 76%
“…It has recently been shown by Dawes et al 21,22 that the "reef"-like saddle point present in many previous ozone PESs is an artifact of the electronic structure model used to generate the PESs. The new Dawes-LolurLi-Jiang-Guo (DLLJG) PES, obtained with a dynamically weighted 23,24 explicitly-correlated multi-reference configuration interaction [25][26][27] approach with the Davidson correction 28 and spin-orbit correction (DW-MRCI-F12+Q), is "reef"-free, thus qualitatively different from all previous ozone PESs. 16,20,29 The disappearance of the "reef" structure essentially results from the employment of a large basis set, larger active configuration spaces, and dynamical weighting of excited states.…”
mentioning
confidence: 76%
“…Calculations relating to any particular molecular state of interest were performed using a dynamically weighted full-valence CASSCF procedure, focusing maximum weight on the state of interest (the singlet and triplet states were computed separately). 23 This was used as the reference for subsequent Davidson-corrected MRCI(+Q) calculations. The MOLPRO code was used to perform all of the electronic structure calculations reported here.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…15 To briefly summarize, we found that the height of the submerged reef and depth of the vdW well are substantially reduced by both basis set and active space completeness. We followed the switch in character between the ground state and an excited state correlated with O 2 ( 1 g ) + O( 1 D g ) products and noted that if all 13 singlet states were included using a dynamically weighted state-averaged method 25,26 (DW-SA-CASSCF), then the transition was better behaved and the reef all but disappeared. Finally, by including more than one reference state in the internally contracted icMRCI (thus increasing the number of contracted configurations and reducing the effect of internal contraction), we obtained a MEP that is a monotonic function of the distance to the dissociating O-atom (no reef feature).…”
mentioning
confidence: 99%